Tizoxanide Promotes Apoptosis in Glioblastoma by Inhibiting CDK1 Activity - Huang, Si; Xiao, Jingxian; Wu, Junyong; Liu, Jiayi; Feng, Xueping; Yang, Chengdong; Xiang, Daxiong; Luo, Shilin (Frontiers in Pharmacology, 2022)
The antiparasitic drug nitazoxanide (NTZ) has received considerable attention for its potential in cancer therapy. In this study, we demonstrate that tizoxanide (TIZ), an active metabolite of NTZ, exhibits antiglioma activity in vitro and in vivo by inducing G2/M cell cycle arrest and apoptosis. In vitro, TIZ dose-dependently inhibited the proliferation of U87, U118, and A172 human glioblastoma (GBM) cells at 48 h with IC50 values of 1.10, 2.31, and 0.73 µM, respectively. Treatment with TIZ (1 and 10 µM) also dose-dependently inhibited the colony formation of these GBM cells and accumulated ROS damage in the nucleus. In silico target fishing combined with network pharmacological disease spectrum analyses of GBM revealed that cycle-dependent kinase 1 (CDK1) is the most compatible target for TIZ and molecular docking by Molecule Operating Environment (MOE) software confirmed it. Mechanistically, TIZ inhibited the phosphorylation of CDK1 at Thr161 and decreased the activity of the CDK1/cyclin B1 complex, arresting the cell cycle at the G2/M phase. TIZ may induce apoptosis via the ROS-mediated apoptotic pathway. In vivo, TIZ suppressed the growth of established subcutaneous and intracranial orthotopic xenograft models of GBM without causing obvious side effects and prolonged the survival of nude mice bearing glioma. Taken together, our results demonstrated that TIZ might be a promising chemotherapy drug in the treatment of GBM.